Expression profile of human herpesvirus 8 (HHV-8) in pyothorax associated lymphoma and in effusion lymphoma. Issue 2 (1st April 2001) - O'Donovan, M; Silva, I; Uhlmann, V; Bermingham, N; Luttich, K; Martin, C; Sheils, O; Killalea, A; Kenny, C; Pileri, S; O'Leary, J J
Abstract : Aims —Pyothorax associated lymphoma (PAL) occurs in a clinical setting of longstanding pyothorax or chronic inflammation of the pleura. Like primary effusion lymphoma, it has an association with Epstein-Barr virus (EBV), and is confined to the pleural cavity, but has differing morphological and phenotypic features. Human herpesvirus 8 (HHV-8) has been consistently reported in primary effusion lymphoma. This study examines the immunophenotype of two European cases of PAL, investigates the presence of HHV-8 and its expression profile, and assesses whether PAL is similar to other effusion lymphomas. Methods —Material was obtained from two European cases of PAL. Immunocytochemical analysis was performed using antibodies against CD45, CD20, CD79a, CD45RAA, CD3, CD43, CD45RO (UCHL1), CD30, BCL-2, CD68, epithelial membrane antigen (EMA), BCL-6, p53, Ki-67, κ light chain, λ light chain, and the EBV antigens latent membrane protein 1 (LMP-1) and EBV encoded nuclear antigen 2 (EBNA-2). The cases were examined for HHV-8 by means of polymerase chain reaction in situ hybridisation (PCR-ISH), solution phase PCR, in situ hybridisation (ISH), and real time quantitative TaqMan PCR to HHV-8 open reading frame 26 (ORF-26) and viral (v) cyclin encoding regions. The expression profile of HHV-8 in PAL and in BC-1 and BC-3 cells was assessed by RNA TaqMan PCR to the HHV-8 genes encoding v-cyclin, v-IL-6, and G protein coupled receptor (GPCR). Results —Both cases expressed CD24, CD20, CD79a, BCL-2, light chain restriction, and high Ki-67 staining. EBV was identified by EBER-ISH in one case. HHV-8 was not identified by solution phase PCR, but was detected by PCR-ISH (sensitivity of 1 viral genome copy/cell) in 35% of the cells and by TaqMan PCR, which showed 50–100 HHV-8 copies/2000 cell genome equivalents (sensitivity of 1 viral genome in 10 6 contaminating sequences). HHV-8 v-IL-6, v-cyclin, and GPCR encoded transcripts were identified using RNA TaqMan PCR. v-IL-6 was high in PAL and in BC-1 and BC-3 cells. Conclusion —The presence of HHV-8 in one of two patients with PAL raises interesting questions in relation to the pathobiology of the condition. Clearly, the results indicate that HHV-8 is not an obligate pathogen, necessary for the effusion phenotype, but might contribute to it by its secretion of specific cytokines.